(untitled) (Actualizaciones en Sida e Infectología, 2023)
Multiple opportunistic infections can manifest simultaneously when immunosuppression is severe in patients infected with the human immunodeficiency virus. A case of co-infection with HIV, Bartonella spp and Mycobacterium kansasii is presented, with few reports to date of this association and even more so in patients who are unaware of their HIV status.